EDUCATION ON THE USE OF AROMATIC GINGER AS AN ANTI-INFLAMMATORY IN TANI BHAKTI VILLAGE, KUTAI KARTANERAGA - Febrina Mahmudah; Sabaniah Indjar Gama; Victoria Yunita Fitriani; Onny Ziasti Fricillia; Jainudin; Indriya Pijaryani; Noor Linda F (Jurnal Sinergitas PKM & CSR, 2025)
Kencur as aromatic ginger (Kaempferia galanga L.) is a spice that is often used to season food in Indonesia, giving it a distinctive aroma and flavor. In addition, kencur can be used empirically for traditional medicinal purposes, one of which is as an anti-inflammatory. Inflammation is the immune system's response to harmful stimuli, such as pathogens, damaged cells, toxic compounds, or radiation, and acts by removing harmful stimuli and initiating the healing process. The purpose of this activity is to provide education to increase public knowledge about the benefits of kencur as an anti-inflammatory. The method used in this activity was counseling about kencur that can be used as an anti-inflammatory on 20 respondents. The evaluation of the results of the activity to increase knowledge was carried out through a pretest and posttest. The obtained values were statistically analyzed using the t-Test: Paired Two Sample for Means data analysis with a significance level of 0.05. The evaluation results showed that the significance level was < 0.05, indicating an increase in participants' knowledge about ginger as an anti-inflammatory agent.